2011
DOI: 10.1088/0953-8984/23/19/194111
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour of binary mixtures of diamagnetic colloidal platelets in an external magnetic field

Abstract: Using fundamental measure density functional theory we investigate paranematic-nematic and nematic-nematic phase coexistence in binary mixtures of circular platelets with vanishing thicknesses. An external magnetic field induces uniaxial alignment and acts on the platelets with a strength that is taken to scale with the platelet area. At particle diameter ratio λ = 1.5 the system displays paranematic-nematic coexistence. For λ = 2, demixing into two nematic states with different compositions also occurs, betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Third, the critical and triple lines could potentially intersect in the three-dimensional (temperature−pressure-field strength) phase diagram, resulting in the appearance of tricritical, "double-critical", and "criticaltriple" points. 20,47,69,70 We note that all these rich and varied phase diagram morphologies have been already observed in extensive theoretical studies of simple "spin fluids" in external fields. 71−75 The important difference of semiflexible polymers from these well-studied systems is the presence of an additional control parameter, i.e.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Third, the critical and triple lines could potentially intersect in the three-dimensional (temperature−pressure-field strength) phase diagram, resulting in the appearance of tricritical, "double-critical", and "criticaltriple" points. 20,47,69,70 We note that all these rich and varied phase diagram morphologies have been already observed in extensive theoretical studies of simple "spin fluids" in external fields. 71−75 The important difference of semiflexible polymers from these well-studied systems is the presence of an additional control parameter, i.e.…”
Section: Introductionsupporting
confidence: 52%
“…It will be shown that the phase diagram morphology is governed by a delicate interplay between the chain stiffness κ and the field strength ϕ, which will result in various nontrivial effects, such as the appearance of "double critical" and "critical triple" points. 20,47,69,70 Before addressing this complicated scenario, we begin by studying the good solvent case in Section 3.1, where there are only two relevant intensive variables pressure and field strength parameter.…”
Section: Microscopic Model and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydispersity reportedly expands the biphasic region in the phase diagram as a function of concentration. , However, the effect of the polydispersity of GO particles on electro-optical switching has not been explored. The application of electric fields to an isotropic GO colloid induces antinematic ordering of GO particles, and the field-induced ordering behavior of the antinematic binary mixture can produce quite new phenomena. , …”
mentioning
confidence: 99%
“…The application of electric fields to an isotropic GO colloid induces antinematic ordering of GO particles, 28 and the field-induced ordering behavior of the antinematic binary mixture can produce quite new phenomena. 29,30 In this study, we investigate electro-optical switching of binary mixtures of two GO colloids with small and larger GO particles, where the GO concentration is adjusted to be constant. Interestingly, the addition of a small amount of large GO particles into a colloid containing small GO particles dramatically enhances the electro-optical birefringence.…”
mentioning
confidence: 99%